Rancang Bangun Sistem Informasi Pelayanan Hukum Menggunakan Metode Personal Extreme Programming Pada Pusat Layanan Hukum Institut Teknologi Kalimantan - Dwi Nur Amalia; Fahmi Fauzan Firman; Sri Rahayu Natasia; Farida Nur Hidayah; Aidil Saputra Kirsan (Jurnal Teknik Elektro dan Komputer TRIAC, 2025)
Each institution has services that play an important role in supporting smooth operations, just as the Kalimantan Institute of Technology (ITK) has legal services through the Legal Service Center (PLH). PLH is tasked with providing administrative support and legal information to the academic community. However, in its implementation, PLH faces various obstacles such as existential challenges related to clarity of roles, duties, services, and functions, as well as a lack of transparency, especially in the process of making the Rector's Decree. In addition, the lack of an integrated system causes service data management to be scattered, causing inefficiencies in data management and business processes that run on each service. To overcome these problems, a website-based Legal Service Information System was developed using the Personal Extreme Programming (PXP) method with stages of system needs analysis, planning, iteration initiation, design, implementation, system testing, and retrospective. This system was developed using the Laravel framework with features such as checking the status of decision letters, reviewing memoranda  of understanding and agreements, reviewing rector regulations, and legal consultation. The system was completed by the developers with 6 iterations and 41 user stories. There are 4 main actors: the head of PLH, PLH staff, rectorate staff, and users. The test was carried out using the black box testing method in each iteration with the Legal Service Center of the Kalimantan Institute of Technology, and the results were in accordance and successfully carried out.